Pathology and parasitology of free-ranging coyotes from Tennessee and South Carolina. - Eliza Baker; Michelle Dennis; Debra Miller; Chunlei Su; Alexa Rosypal von Dohlen; Mohamed A Abouelkhair; Sarah A Hamer; Alex Jensen; Richard Gerhold (PLoS ONE, 2025)
Coyotes are exposed to many parasites and pathogens of veterinary and zoonotic concern. To assess the prevalence of the diseases caused by these microbes, we opportunistically obtained coyote samples from a variety of sources including a GPS collaring study, rabies testing facilities, wildlife resources agents, and road-side mortalities. We performed necropsies, serological testing, fecal flotations, and molecular analyses on coyotes from Tennessee and South Carolina. Dirofilaria immitis (heartworm) infected 46% (41/89) of coyotes and was associated with eosinophilic alveolitis and arteritis. Paragonimus kellicotti, a zoonotic lung fluke, was found in 24% (17/71) of Tennessee coyotes, including one coyote with extrapulmonary infection affecting the liver and lymph nodes. Trichinella spp., a zoonotic nematode, was present in 17% (12/71) of Tennessee coyotes but was not associated with muscular inflammation. Sarcoptes scabiei, the causative agent of sarcoptic mange, was detected in one Tennessee coyote. Most coyotes (86% [90/105]) were seropositive for Toxoplasma gondii, while 8.5% (9/106) were seropositive for Trypanosoma cruzi, an emerging zoonotic, vector-borne parasite. This study demonstrated that coyotes are commonly exposed to numerous parasites and pathogens that affect people and pets and are excellent sentinels for these diseases.